1984
DOI: 10.3758/bf03332187
|View full text |Cite
|
Sign up to set email alerts
|

Psychological theories of hippocampal function

Abstract: Theories and models of the hippocampus have typically linked this structure to various psychological processes, for example, internal inhibition, response inhibition, attentional shift, attentional "tuning out," recognition memory, long-term memory selection, contextual retrieval, spatial memory, working memory, and chunking. Predictions made from various models are contrasted with reproducible hippocampal lesion data obtained from various experimental paradigms: habituation to novelty, acquisition, extinction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 68 publications
(132 reference statements)
0
32
0
Order By: Relevance
“…For example, the work of Kim and Fanselow (1992) and Anagnostaris et al (1999) employed a fearconditioning paradigm to show a recent memory loss for contextual information. Inasmuch as contextual processing has reliably been shown to depend on the hippocampus in anterograde studies (Good & Bannerman, 1997;Good & Honey, 1991;Schmajuk, 1984), it is reasonable to expect amnesia for similar types of information in a retrograde paradigm (e.g., Anagnostaris et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the work of Kim and Fanselow (1992) and Anagnostaris et al (1999) employed a fearconditioning paradigm to show a recent memory loss for contextual information. Inasmuch as contextual processing has reliably been shown to depend on the hippocampus in anterograde studies (Good & Bannerman, 1997;Good & Honey, 1991;Schmajuk, 1984), it is reasonable to expect amnesia for similar types of information in a retrograde paradigm (e.g., Anagnostaris et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Lesion studies have revealed a number of behavioral processes for which the integrity of the hippocampus is critical, most prominently, tasks that require processing of spatial information (O'Keefe and Nadel, 1978: Olton et al, 1979: Chozick, 1983: Morris, 1983Schmajuk, 1984), while hippocampal lesion effects related to so-called nonspatial behavior have been reported less frequently but fairly regularly (Gray, 1982;Schmajuk, 1984;Rawlins, 1985;Tonkiss et al, 1988: Sutherland et a]., 1989Jagielo et al, 1990). The data from these correlational studies are congruent with lesion data in revealing an important involvement of hippocampal circuitry in swimming navigation, particularly in its purest form: reversal learning and crossing over the former platform location.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Such a view conforms to the emerging computational view of distributed neural representation [10] [11]. The hippocampus function could better be described in terms of computational-representational activity, e.g., analyzing, synthesizing, comparing, storing, detecting and encoding the representations of different events [12]. The computational view of the hippocampus raises the question of neural code for the sensory information processing.…”
Section: Introductionmentioning
confidence: 83%